Selecting future teachers: the predictive validity of communication skills, personality and academic achievement in the admission process at an Asian University/ Richard J. Holmes, Marina Mohamed Arif and Lee Lai Fong - Richard J., Holmes; Marina, Mohamed Arif; Lee Lai, Fong (ACRULeT, Faculty of Education & UiTM Press, 2009)
This paper studies the relationship between communication skills, personality factors and performance in secondary school and academic success in Teaching English as a Second Language (TESL) programme in a Malaysian university. It was found that three specific skills: fluency, clarity and language use were modestly predictive of success over the first six semesters of the degree programme but that personality traits and general and educational knowledge were not. Performance on the Malaysian secondary school examination, especially in maths, also predicted academic success. It was also found that the qualities assessed at the interview were barely detectable by lecturers a little more than two years later although communicative skills were somewhat more so than the others. The findings suggest that when students are studying in the medium of a second language, communicative competence and prior academic achievement, possibly reflective of underlying general intelligence are important factors contributing to academic success.